A Review of Advance Directives As Per Mental Health Care Act 2017 - Sharjeel Khan1 , Shadma Quazi2 , Ranjit Ambad3 , Ragini Patil4 , Ajinkya S. Ghogare3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The year 2017 is surely a milestone year for the professionals of mental health and the mentally ill patients.The year marks the historic moment of the Mental Health Care Act (MHCA). The utmost significance of thisact cannot be ignored because it has come as a ray of hope because, for the first time, people with mentalillness have been granted few rights, such as the right of the mentally ill person to make advance directives.Hence, it can be said that its arrival is an important accomplishment and a ray of hope for the millions ofmentally ill people. It is an important critical step in addressing mental illness and focuses the public’sattention on the current status of the mentally ill patients. The attempts to have its implementation wouldsurely face several challenges. Understanding the values relevant to ADs is important for clinicians becausethey have a major role to act in coping with severe and chronic mentally ill person. The object of this articleis to gather the brilliant flashes and the boring aspects as well as drawbacks of the act. To start recognizingthe strengths and anticipating challenges in their implementation and the future solution.